Poverty, food Prices, and dietary choices in Malawi - Pauw, Karl; Verduzco-Gallo, Íñigo; Ecker, Olivier (International Food Policy Research Institute, 2015)
In this chapter we analyze Malawi’s recent food consumption trends, including per capita calorie and micronutrient-consumption estimates, and reflect on how these pertain to (1) changes in poverty and household income, and (2) relative changes in food prices. In so doing, we extract from a detailed analysis of household food consumption (Verduzco-Gallo, Ecker, and Pauw 2014) and from an assessment of recent poverty trends (Pauw, Beck, and Mussa 2014). Both these studies draw on the two latest rounds of Malawi’s nationally-representative Integrated Household Surveys (IHS2 and IHS3) collected in 2004–2005 and 2010–2011 (NSO 2005; 2012b).